2021
DOI: 10.1002/cncr.33483
|View full text |Cite
|
Sign up to set email alerts
|

Active surveillance of patients who have sentinel node positive melanoma: An international, multi‐institution evaluation of adoption and early outcomes after the Multicenter Selective Lymphadenectomy Trial II (MSLT‐2)

Abstract: Background For patients with sentinel lymph node (SLN)‐positive cutaneous melanoma, the Second Multicenter Selective Lymphadenectomy trial demonstrated equivalent disease‐specific survival (DSS) with active surveillance using nodal ultrasound versus completion lymph node dissection (CLND). Adoption and outcomes of active surveillance in clinical practice and in adjuvant therapy recipients are unknown. Methods In a retrospective cohort of SLN‐positive adults treated at 21 institutions in Australia, Europe, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…Over half of the respondents still selectively use immediate CLND, despite the lack of high‐level evidence to support this practice 2 . A recent retrospective study confirmed this change in practice with 86% of patients in their post‐publication of MSLT2 cohort of 965 positive SLNBs receiving active surveillance 7 …”
Section: Discussionmentioning
confidence: 99%
“…Over half of the respondents still selectively use immediate CLND, despite the lack of high‐level evidence to support this practice 2 . A recent retrospective study confirmed this change in practice with 86% of patients in their post‐publication of MSLT2 cohort of 965 positive SLNBs receiving active surveillance 7 …”
Section: Discussionmentioning
confidence: 99%
“…As reported in this issue of C ancer , Broman and colleagues 14 recently examined the adoption and early outcomes of active surveillance for patients who had primary cutaneous melanoma and a positive SLN between mid‐2017 and late 2019 and whose management was likely informed by the recently published MSLT‐II and DeCOG‐SLT randomized clinical trials. Remarkably, this analysis includes clinicopathologic, treatment, follow‐up, and recurrence data comprised of 1154 SLN‐positive patients from 21 institutions from the United States, Australia, and Europe that, together, contributed to a robust data set to perform these exploratory studies.…”
mentioning
confidence: 99%
“…Among the patients who underwent CLND, Broman and colleagues noted that they were more likely to be younger, have a head and neck primary, or have high‐risk primary and/or regional factors (including increased tumor thickness, more positive SLNs, extranodal extension, increased SLN tumor burden, or microsatellite disease). On multivariable analysis, patients who had clinicopathologic features often considered under‐represented in the MSLT‐II study cohort, including a head and neck primary (13.7% of patients in MSLT‐II), high SLN tumor burden (33.9% of patients had >1.0 mm maximum SLN tumor dimension in MSLT‐II), or a high number of SLNs (<3% of patients had ≥3 positive SLNs in MSLT‐II), were more likely to undergo CLND 11,14 . It is notable that several clinicopathologic factors that portend an increased risk of tumor‐involved non‐SLNs at CLND—eg, thicker primary tumors, higher SLN tumor burden—have also been associated with decreased MSS 15 .…”
mentioning
confidence: 99%
“…Again, this is consistent with clinical observation and practice, where advanced surgery is routinely utilized to manage lymph node disease which can create long-term irreversible morbidity for the patient, most notably, lymphoedema. However, based on evidence from trials such as MSLT-2 and DeCOG-SLT, clinical practice has begun to shift away from immediate surgery of confirmed nodal disease and towards observation [51,52]. As such, a corresponding future increase in MSS score is expected.…”
Section: Discussionmentioning
confidence: 99%